GenARDIS rewards bright ideas - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
A dedicated cellular phone network for women working in Lesotho s agricultural sector and a training video used for promoting gender advocacy in Tonga. These were just two of the winning ideas that caught the eye of the judges in this year s GenARDIS